Factors Affecting the Implementation of e-Surat Applications at Regional Apparatus Organizations in Tabanan Regency - Juliantara, I Wayan Ady; Sariyasa; Sunarya, I Made Gede (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The development of information technology has given birth to many new innovations, such as the e-Surat application which can help the administrative process of electronic service manuscripts at the OPD (Regional Apparatus Organization) in Tabanan Regency. The implementation of the e-Surat application on OPD in Tabanan Regency is still not optimal, there are factors that affect the implementation of the e-Surat application on OPD in Tabanan Regency. The model or method that is considered appropriate for analyzing and understanding the factors that can affect the implementation of the e-Surat application on OPD in Tabanan Regency is the TOE framework that will analyze the implementation of the e-Surat application on OPD in Tabanan Regency in terms of technology, organization and environment aspects. Data analysis techniques use multiple linear regression analysis. The results of the data analysis show that: (1) technological variables have a positive and significant effect on the implementation of e-Surat applications in OPD in Tabanan Regency, (2) organizational variables have a positive and significant effect on the implementation of e-Surat applications in OPD in Tabanan Regency and (3) environmental variables have a positive and significant effect on the implementation of e-Surat applications in OPD in Tabanan Regency.